Experimental investigation on selective laser melting of 17-4PH stainless steel. (January 2017) - Hu, Zhiheng; Zhu, Haihong; Zhang, Hu; Zeng, Xiaoyan
Abstract: Selective laser melting (SLM) is an additive manufacturing (AM) technique that uses powders to fabricate 3Dparts directly. The objective of this paper is to perform an experimental investigation of selective laser melted 17-4PH stainless steel. The investigation involved the influence of separate processing parameters on the density, defect, microhardness and the influence of heat-treatment on the mechanical properties. The outcomes of this study show that scan velocity and slice thickness have significant effects on the density and the characteristics of pores of the SLMed parts. The effect of hatch spacing depends on scan velocity. The processing parameters, such as scan velocity, hatch spacing and slice thickness, have effect on microhardness. Compared to the samples with no heat-treatment, the yield strength of the heat-treated sample increases significantly and the elongation decreases due to the transformation of microstructure and the changes in the precipitation strengthening phases. By a combination of changes in composition and precipitation strengthening, microhardness improved. Highlights: The separate processing parameters' influence of SLM is investigated. The RN and Dm distribution was used to characterize the defect. The Cu precipitation phase plays an important role in changing the microhardness. The impact of changes in composition and precipitation is proposed.